2017
DOI: 10.5176/2251-1865_cbp17.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religious Identity toward Academic Performance: An Experimental Study

Abstract: Indonesia is known as a multicultural country, including religious diversity. There were many internalhorizontal conflicts happened in Indonesia caused by this diversity. It becomes the most dominant factor that causes many recent conflicts. This study aimed to examine the effect of religious identity toward academic performance. This research was conducted using experiment method. As the sample, 34 students randomly selected from an Islamic University in Indonesia. The result of this study indicates that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Hence, a positive relationship exists between academic behavioural confidence and religiosity. Furthermore, a study conducted by Amaliyah (2017) showed that even the knowledge of the teachers' religious identity was potent enough to influence students' performance at the academic setting. Also, Jeynes (2003) established, in his findings, that religiously committed urban children perform better in most academic measures than their less religious counterparts, despite extraneous variables such as socio-economic status, race, and gender.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Hence, a positive relationship exists between academic behavioural confidence and religiosity. Furthermore, a study conducted by Amaliyah (2017) showed that even the knowledge of the teachers' religious identity was potent enough to influence students' performance at the academic setting. Also, Jeynes (2003) established, in his findings, that religiously committed urban children perform better in most academic measures than their less religious counterparts, despite extraneous variables such as socio-economic status, race, and gender.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Banyak orang tua yang tidak mendapatkan pendidikan seksual sewaktu kecil (Amaliyah & Nuqul, 2017;Ballard & Gross, 2009), sehingga orang tua tidak mengerti bagaimana memulainya. Orang tua tidak memiliki pengetahuan dan keterampilan dalam memberikan pendidikan seksual (Martin et al, 2018;Turnbull et al, 2008).…”
Section: Pendahuluanunclassified
“…So, the language that use in our communication must be meaningful avoid misunderstanding or misinterpretation between speaker and listener or we can add writer and reader (Ahmad, Ahmad, & Masood, 2020). Amaliyah, Anwar, & Nuqul, (2017) illustrated listening to music is not just a hobby or the teenagers, particularly but has also become a favorite source of amusement or entertainment. Mostly, people listen to music while doing their chores or doing daily routine tasks, such as studying, working, and eating and even during sleeping.…”
Section: Introductionmentioning
confidence: 99%